Care partners and consumer health information technology: A framework to guide systems‐level initiatives in support of digital health equity - Jennifer L. Wolff; Aleksandra Wec; Danielle Peereboom; Kelly T. Gleason; Halima Amjad; Julia G. Burgdorf; Jessica Cassidy; Catherine M. DesRoches; Chanee D. Fabius; Ariel R. Green; C. T. Lin; Stephanie K. Nothelle; et al. (Wiley, 2024)
Abstract Introduction Consumer‐oriented health information technologies (CHIT) such as the patient portal have a growing role in care delivery redesign initiatives such as the Learning Health System. Care partners commonly navigate CHIT demands alongside persons with complex health and social needs, but their role is not well specified. Methods We assemble evidence and concepts from the literature describing interpersonal communication, relational coordination theory, and systems‐thinking to develop an integrative framework describing the care partner's role in applied CHIT innovations. Our framework describes pathways through which systematic engagement of the care partner affects longitudinal work processes and multi‐level outcomes relevant to Learning Health Systems. Results Our framework is grounded in relational coordination, an emerging theory for understanding the dynamics of coordinating work that emphasizes role‐based relationships and communication, and the Systems Engineering Initiative for Patient Safety (SEIPS) model. Cross‐cutting work systems geared toward explicit and purposeful support of the care partner role through CHIT may advance work processes by promoting frequent, timely, accurate, problem‐solving communication, reinforced by shared goals, shared knowledge, and mutual respect between patients, care partners, and care team. We further contend that systematic engagement of the care partner in longitudinal work processes exerts beneficial effects on care delivery experiences and efficiencies at both individual and organizational levels. We discuss the utility of our framework through the lens of an illustrative case study involving patient portal‐mediated pre‐visit agenda setting. Conclusions Our framework can be used to guide applied embedded CHIT interventions that support the care partner role and bring value to Learning Health Systems through advancing digital health equity, improving user experiences, and driving efficiencies through improved coordination within complex work systems.